Systematic review of the technical and physiological constraints of the Orion Multi-Purpose Crew Vehicle that affect the capability of astronauts to exercise effectively during spaceflight. (May 2020) - Laws, J.M.; Caplan, N.; Bruce, C.; McGrogan, C.; Lindsay, K.; Wild, B.; Debuse, D.; Wotring, V.; Winnard, A.
Abstract: Background: The constraints of the Orion Multi-Purpose Crew Vehicle present challenges to the use of current exercise countermeasures necessary to prevent severe deconditioning of physiological systems during microgravity exposure beyond Low Earth Orbit. The purpose of this qualitative systematic review was to determine the technical constraints of the Orion Multi-Purpose Crew Vehicle which may hinder astronauts' capabilities to effectively exercise during long distance spaceflight. Methods: Databases were searched from the start of their records to December 2018. Included documents were quality assessed with the AMSRG quality scoring tool and Thematic Analysis was used to analyse the included documents to assess technical constraints of the Orion Multi-Purpose Crew Vehicle. Results: 19 studies were included in the final review. All identified constraints, other than data transmission limitations, were found to ultimately be a result of the volume and upload mass constraints of the Orion Multi-Purpose Crew Vehicle. There was a lack of detailed studies and lack of consistency in specifying spacecraft in the literature that limit the conclusions of this review. Conclusion: Space agencies are advised to ensure that information on relevant spacecraft constraints is readily available to researchers. This information should be made accessible in an official published document as opposed to disparate and grey literature, and include quantitative information rather than qualitative summaries. Highlights: Qualitative systematic review of the technical constraints of the Orion spacecraft. Volume and upload mass constraints hinder the capability of astronauts to exercise effectively. There is a lack of detailed studies and lack of consistency in specifying spacecraft in the available literature.